An update on liver transplantation: A critical review. (January 2016) - Neuberger, James
Abstract: Liver transplantation, although now a routine procedure, with defined indications and usually excellent outcomes, still has challenges. Donor shortage remains a key issue. Transplanted organs are not free of risk and may transmit cancer, infection, metabolic or autoimmune disease. Approaches to the donor shortage include use of organs from donors after circulatory death, from living donors and from those previously infected with Hepatitis B and C and even HIV for selected recipients. Normothermic regional and/or machine perfusion, whether static or pulsatile, normo- or hypothermic, are being explored and will be likely to have a major place in improving donation rates and outcomes. The main indications for liver replacement are alcoholic liver disease, HCV, non-alcoholic liver disease and liver cancer. Recent studies have shown that selected patients with severe alcoholic hepatitis may also benefit from liver transplant. The advent of new and highly effective treatments for HCV, whether given before or after transplant will have a major impact on outcomes. The role of transplantation for those with liver cell cancer continues to evolve as other interventions become more effective. Immunosuppression is usually required life-long and adherence remains a challenge, especially in adolescents. Immunosuppression with calcineurin inhibitors (primarily tacrolimus), antimetabolites (azathioprine or mycophenolate) and corticosteroids remains standard. Outcomes after transplantation are good but not normal in quality or quantity. Premature death may be due to increased risk of cardiovascular disease, de novo cancer, recurrent disease or late technical problems. Highlights: Organ shortage remains the biggest challenge facing liver transplantation. New approaches include greater use of split livers and use of organs from higher risk donors and donors after circulatory death. Machine perfusion is likely also to make a significant impact on the quality and quantity of the donor pool. Long term survival is limited by vascular disease, de novo cancer, recurrent disease and infection.